Laser surgery reveals the biomechanical and chemical signaling functions of aphid siphunculi (cornicles). - Serine Alfaress; Craig R Brodersen; El-Desouky Ammar; Michael E Rogers; Nabil Killiny (PLoS ONE, 2018)
Aphids are an attractive food source to many predators and parasitoids because of their small size, soft bodies and slow movement. To combat predation, aphids evolved both behavioral and chemical defensive mechanisms that are operated via siphunculi (cornicles), differently developed structures that more or less extend from their abdomen. Although both direct and indirect linkages between siphunculi and their defensive mechanisms have been explored, their ultimate effects on aphid fitness are still broadly debated. To explicitly test the influence of siphunculi on brown citrus aphid, Aphis (Toxoptera) citricida (Kirkaldy), fitness, we razor-cut and laser-sealed the siphunculi. Siphunculi removal resulted in two distinct behavior modifications, (false aggregation and increased drop-off rates) that led to decreased survival and the loss of the ability to right themselves from an inverted position. These results together indicate that siphunculi play an important role in survival, and removal of these organs will have negative effect on aphid fitness. Furthermore, results suggested that released alarm pheromone may play an important role in communication among aphid clone-mate, and omitting it results in miscommunication and competition among clonemates. These findings will help in better understanding the aphid biology.